Potensi Bencana Alam Gempa Bumi dan Gerakan Tanah, di Kawasan Taman Nasional Gunung Ciremai dan Sekitarnya - Djaja, Djaja; Pratomo, Indyo (JURNAL BIOLOGI INDONESIA, 2009)
ABSTRACTThe natural dissarter and Land Slide at Ciremai Mountain National Park. Kuningan region,West Java, has relatively highly potential on the seismic and land slide hazards. This region issituated on the active tectonics, deep slopes and generally composed by volcanic sediments ofCiremai volcano. All of those factors are, even more, situated on the annually high rainfallregion. The fractures and deformation of the soil and landforms triggered by the earthquakesalso an important factor facilitate the land slides.Keyword: Kuningan, West Java, seismic hazard, earthquake,land slide hazard